Sustainable Urban Development and Management: A case study of Nelson Mandela Bay Metropolitan Municipality (Gqeberha) - Goliath, Lloyd (Department of Construction Economics and Management, 2024)
As Bell & Morse (2018) argued, sustainable development has been notoriously difficult to pin down over time based on the themes, level and the agents that benefit from it. As a result, most indicators to measure sustainability have been binary targets that did not measure the full extent of the sustainability pillars in urbanisation. This study explores urban management and sustainability development in Nelson Mandela Bay Metro (NMBM) and attempts to determine its sustainability on the four dimensions of sustainability: society, economy, environment, and the institutional framework. The research methodology is a single case study of NMBM using a mixed methods approach consisting of structured questionnaires to residents, semi-structured interviews of ‘sustainability officials' and secondary data (literature review) from credible sources. The research findings are that NMBM, as with all South African metros has strong frameworks and guidelines for sustainability but the frameworks are poorly implemented. According to the survey and interviews to residents and ‘sustainability officials' respectively in the metro and secondary data (mainly from NMBM and South Africa Cities Network websites), NMBM appears to be regressing on its sustainability and green economy drive. An analysis of the results of the study point to a metro regressing on most dimensions of sustainability with limited sustainability initiatives pursued in a few areas (e.g., energy). The residents' survey found NMBM to be unsustainable (48.4% unsustainable, 28.3% indifferent and 23.3% sustainable) in all the four pillars of sustainability (40.6% economic, 52.2% socio-cultural, 61.7% environment and 38.9% institutional). The management of the water crisis and instability in the metro's leadership, are manifestations of the metro's continued unsustainable management of the city. Recommendations which are consistent with Maslow's hierarchy of needs principle, calls for the metro to manage basic service provision (establishing a stable leadership, managing the water and energy crisis, and improving compliance with its legal universe) before refocusing on the bigger sustainable urban development agenda.